Dentist education and labour market in Mexico: elements for policy definition - González-Robledo Luz; González-Robledo María; Nigenda Gustavo (BMC, 2012)
Abstract Background Here, the educational and labour market characteristics of Mexican dentists are revised. Dentistry is a health profession that has been scarcely studied in developing countries. This analysis attempts to understand the relationships and gaps between the supply and demand of dentists in the country. Around 5000 new dentists graduate every year looking for a place in the labour market. Methods A cross-sectional study with exploratory, descriptive and correlational scope was carried out between 2006 and 2008. Analyses of quantitative data on dentists from national surveys and occupational statistics were complemented with qualitative information provided by 43 key informants in five Mexican states. Results The 2008 dentist labour market can be characterized as follows: 75% worked in the private sector, most of them independently; more than two-thirds were women; the proportion of specialists was low (slightly more than 10%); unemployment was more than 20% and labour wastage was nearly 40%, with most wastage corresponding with female dentists. The increase in the number of dentists entering the labour market during the last two decades is more related to the educational market than to the population's health needs and the number of dentists actually required to meet them. Conclusions The problems identified in the Mexican dentist labour market necessitate urgent intervention on behalf of regulatory bodies in order to balance the tendencies of supply and demand in the number of trained professionals as well as in their incorporation into different market areas. Adequate policies are required to increase the likelihood of achieving this objective.